The World Health Organization Reporting System for Lymph Node, Spleen, and Thymus Cytopathology : Part 1 – Lymph Node - Cozzolino, Immacolata; Ehinger, Mats; Calaminici, Maria; Ronchi, Andrea; Al-Abbadi, Mousa A.; Barroca, Helena; Bode-Lesniewska, Beata; Chhieng, David F.; Katz, Ruth L.; Lin, Oscar; Medeiros, L. Jeffrey; Pitman, Martha Bishop; et al. (Acta Cytologica, 2025)
Background: Fine-needle aspiration biopsy (FNAB) of lymph nodes is a widely used method for evaluating lymphadenopathy. FNAB offers general advantages of rapid turnaround time, low cost and minimal morbidity, and more specific advantages in various clinical situations, such as deeply located lymph nodes or patients with significant comorbidities. The FNAB sample can be utilized for a wide range of ancillary tests, including microbiological studies, immunocytochemistry for primary and metastatic neoplasms and flow cytometry immunophenotyping in cases of lymphoid-rich samples, where there is a suspicion for lymphomas. Summary: The increasing application of FNAB in lymph node pathology has led to the development of a standardized reporting system, formalized in the World Health Organization (WHO) Reporting System for Lymph Node, Spleen and Thymus Cytopathology (WHO System). This system is equally applicable to lymph node, spleen and thymus; however, this article focuses on lymph nodes. The WHO System was established through a joint project of the WHO, the International Agency for Research on Cancer (IARC) and the International Academy of Cytology (IAC) and is structured into five diagnostic categories: inadequate/insufficient/non-diagnostic, benign, atypical, suspicious for malignancy, and malignant. The WHO System provides a standardized and reliable means of categorizing various lymph node lesions based on cytopathology findings and enables pathologists to make more accurate and reproducible diagnoses, thereby improving clinical management and treatment decisions. Integrating cellular morphology and clinical-imaging data help distinguish benign from malignant lesions, significantly reducing diagnostic variability. The primary goal was to reduce diagnostic uncertainty and improve patient outcomes through greater consistency and clarity in lymph node cytopathology reports. The WHO System emphasizes the use of rapid on-site assessment (ROSE) to improve diagnostic accuracy and reduce the need for additional diagnostic procedures. The risk of malignancy (ROM) varies by diagnostic category, with higher risks of malignancy in the “Suspicious for malignancy” and “Malignant” categories. The system also includes recommendations for ancillary tests and performance of additional biopsies when further clarification is needed. The WHO System represents a significant advancement in the standardization of lymph node, spleen, and thymus cytopathology, facilitating interdisciplinary communication and improving risk stratification. However, diagnostic challenges remain, particularly in managing inadequate samples and interpreting atypical lesions, necessitating a multidisciplinary approach that integrates clinical, imaging, ancillary testing and, in some cases, core needle, or excision biopsy material. Key messages: The WHO System serves as a crucial tool for refining the diagnosis of the broad range of inflammatory, infectious, metastatic, and lymphomatous processes in lymph node pathologies. In addition, it is suitable for high income as well as most obviously low- and middle-income countries leading to optimizing therapeutic decision-making.
Keywords: Fine-needle aspirate biopsy; International Academy of Cytology; Lymph node; WHO Reporting System for Cytopathology